Effects of Substituting La and Zn in Disordered Sr₂FeMoO₆ - Le, Duc Hien; Dao, Thi Thuy Nguyet; Nguyen, Phuc Duong (Old Journal, 2019)
The Sr₂₋ₓLaₓFeMoO₆ (x = 0, 0.1, 0.2, 0.3, 0.4) and Sr₂Fe₁₋ₓZnₓMoO₆ (x = 0.05, 0.1, 0.15) samples were prepared using a sol-gel route followed by heat-treatment. X-ray diffraction (XRD), field-emission scanning electron microscope (FESEM) were employed to characterize phase formation and morphology. Magnetization curves in the temperature range 88–430 K were measured by means of a vibrating sample magnetometer (VSM) from which the magnetic moment at 0 K and Curie temperature were determined. The antisite disorder in the samples was evaluated based on the magnetic moment data and the substitution levels. The effects of La and Zn substitution on the magnetic parameters were discussed.